Jeffrey fluid flow and heat transfer past a stretching sheet with Ohmic dissipation - Ahmad, Kartini; Wahid, Zaharah (2015)
This paper considers a mathematical analysis for steady two-dimensional boundary layer flow and heat transfer of a Jeffrey fluid over a stretched sheet. The thermal boundary layer equation takes into account the effect of viscous dissipation along with Ohmic dissipation due to a transverse magnetic field and electric field. The highly non-linear momentum and thermal boundary layer equations are transformed into similarity equations by introducing suitable transformations which are then solved numerically using an implicit finite difference scheme known as the Keller-box method. The numerical solutions for the skin friction coefficient, heat transfer coefficient and the velocity and temperature profiles are computed for various physical parameters, such as Deborah number β, Hartmann number Ha, local electric parameter E1, Eckert number Ec and Prandtl number Pr with λ1, is held fixed (=0).